Towards a Penal Law for Religious? : Consecrated Life in the Light of Pope Francis’s 2021 Reform of Book VI of the CIC. Part I: General Considerations - Skonieczny, Piotr (Prawo Kanoniczne, 2025)
The author analyses the discipline of religious life from the perspective of penal law in the light of Pope Francis’s recent reform of Book VI CIC/21 of 2021. The author asks whether it is possible to speak of a penal law for religious after the reform of Book VI of 2021. The first of the two articles is devoted to general questions. With regard to the sources of criminal law, the author notes that the reform of 2021 does not make any changes in this regard, but it could give an impetus to the introduction of appropriate norms in the proper laws of institutes of consecrated life (I.1.). According to the author, the amendment of Book VI CIC/21 did not take into account the requirements of the discipline of the consecrated life (I.2.). The legislator has maintained the previous legislative technique of the 1983 Code by not providing for special delicts and penalties only for religious (I.2.2.3.). The only significant change is the extension of criminal liability to all consecrated persons in the new canon 1398, § 2 CIC/21 (I.2.2.). With regard to religious, the author argues that one can speak of a double responsibility, penal and disciplinary, which are independent and presuppose a purely disciplinary and not theological conception of the life of the evangelical counsels (I.2.3.). The author distinguishes between the penal precept, referred to in canon 1319, § 1 CIC/21, and the formal precept, which can be provided for in the proper laws of institutes of consecrated life (I.3.). In considering the consecrated person as the author of the canonical delict, the author analyses the common delicts (II.1.), proposing that belonging to the state of consecrated persons is a common aggravating circumstance in accordance with can. 1326, § 1 n. 2 CIC/21 (II.2.). The individual delicts of which religious (II.3.1., II.3.3.) and consecrated persons may be perpetrators are indicated, criticising in this respect canon 1398, § 2 CIC/21 (II.3.2.). Finally, the author notes that dismissal from the institute of consecrated life and from the association of apostolic life is not provided for as a perpetual expiatory penalty in the new canon 1336, § 4, no. 4 and canon 1338, § 1, n. 2 CIC/21 (III.1, III.2). This does not, however, theoretically exclude the inclusion of such a penalty in the proper law on the basis of canons 1312, § 2 and 1336, § 1 CIC/21 (arg. ex can. 1315, § 2 CIC/21 a contrario), although this solution does not seem practical (III.3.).